Analyzing Second Language Written Summaries at University Level - Katarina Zamborova; Blanka Klimova (Emerging Science Journal, 2021)
Objective: The objectives of the study are to identify and categorize non-native students´ errors in the written summaries, to see which research instruments – the mobile reading app (experimental group) or internet-based article (control group) are more effective, and to determine if language proficiency of students will improve. Methods: This study uses an analysis of linguistic-stylistic errors as a research method on the written performance of 29 EFL Slovak students in 29 written summaries. Findings: The findings indicate that the most problematic areas in writing summaries were grammatical (determiners), followed by stylistic (text coherence, slang words, and punctuation), lexical (word collocations), and lexico-stylistic errors (prepositions). Overall, students´ proficiency in both groups rose from B2 to C1 level by 38% of the students (11 students). Therefore, both methods – the reading app and internet-based articles are effective. Novelty: The novelty of the study consists in enriching the existing literature by pointing out errors of EFL Slovak students making in writing summaries by exploiting modern technology in the writing process. Doi: 10.28991/esj-2021-01322 Full Text: PDF